2001
DOI: 10.1039/b104932c
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the nearly diffusion-controlled fluorescence quenching by oxygen of 9,10-dimethylanthracence in liquid solution

Abstract: The rate constant, for the Ñuorescence quenching of 9,10-dimethyl-anthracene (DMEA) by oxygen in k q , n-hexane and methylcyclohexane (MCH) was measured as a function of temperature at 0.1 MPa. It was found that the activation energy for the quenching, was 6.6^0.1 and 8.4^0.3 kJ mol~1, smaller than that for E q E, the solvent viscosity, 7.1^0.2 and 10.6^0.1 kJ mol~1, in n-hexane and MCH, respectively. The E i E, di †erence between and was interpreted to arise as a result of the quenching being not fully but ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Recently, we showed that α ex depends slightly on pressure and is expressed approximately by a polynomial in terms of γη for MCH with large pressure induced solvent viscosity dependence at a constant temperature . In this work, α ex was assumed by Substituting eq 10 into eq 9, we have The plots of γ/ against γη are shown in Figure , together that for pyrene reported previously .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, we showed that α ex depends slightly on pressure and is expressed approximately by a polynomial in terms of γη for MCH with large pressure induced solvent viscosity dependence at a constant temperature . In this work, α ex was assumed by Substituting eq 10 into eq 9, we have The plots of γ/ against γη are shown in Figure , together that for pyrene reported previously .…”
Section: Resultssupporting
confidence: 53%
“…Very recently, the quenching of the S 1 state of pyrene, 9,10-dimethylanthracene, and benzo[ a ]pyrene by oxygen as well as heavy atom quenchers at high pressure was examined, and it was shown that can be separated into the bimolecular rate constant for diffusion, k diff , and that for the quenching, k S,bim , in the solvent cage from the analysis of the pressure-induced solvent viscosity dependence of k q S . The similar analysis was successfully applied for the triplet−triplet annihilation of 2-acetonaphthone that is believed to be diffusion-controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Such cases result from a translational-rotational coupling of diffusion in viscous solvents. We discussed this previously, 20 and R ex was determined by assuming a polynominal in terms of g(σ)η as follows:…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we measured k q for DMEA/O 2 in liquid ethane and propane for which the size, the viscosity, and the density at a given pressure are smaller than those for the solvents studied previously. 17,20,21 The results, together with those in other n-alkanes and methylcyclohexane (MCH) reported previously, are analyzed by eq 6, and the solvent and pressure (density) dependence of the apparent bimolecular quenching rate constant, k bim,0 , in solvent cage as well as the competition of the quenching with diffusion is discussed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation